Biotechnological Potential of Agro-Industrial Wastes as a Carbon Source to Thermostable Polygalacturonase Production in Aspergillus niveus. (20th June 2011) - Maller, Alexandre; Damásio, André Ricardo Lima; Silva, Tony Marcio da; Jorge, João Atílio; Terenzi, Héctor Francisco; Polizeli, Maria de Lourdes Teixeira de Moraes
Abstract : Agro-industrial wastes are mainly composed of complex polysaccharides that might serve as nutrients for microbial growth and production of enzymes. The aim of this work was to study polygalacturonase (PG) production by Aspergillus niveus cultured on liquid or solid media supplemented with agro-industrial wastes. Submerged fermentation (SbmF) was tested using Czapeck media supplemented with 28 different carbon sources. Among these, orange peel was the best PG inducer. On the other hand, for solid state fermentation (SSF), lemon peel was the best inducer. By comparing SbmF with SSF, both supplemented with lemon peel, it was observed that PG levels were 4.4-fold higher under SSF. Maximum PG activity was observed at 55 ∘ C and pH 4.0. The enzyme was stable at 60 ∘ C for 90 min and at pH 3.0–5.0. The properties of this enzyme, produced on inexpensive fermentation substrates, were interesting and suggested several biotechnological applications.